Current concepts in the use of lasers in periodontal and implant dentistry - Georgios Romanos (Wolters Kluwer Medknow Publications, 2015)
Lasers have various periodontal applications including calculus removal (Er: YAG, Er, Cr: YSGG lasers); soft tissue excision, incision and ablation; decontamination of root and implant surfaces; biostimulation; bacteria reduction; and osseous surgery. This paper reviews some of the major opportunities for using lasers in periodontal and implant specialty practices. The literature relating to the use of lasers for removal of the pocket epithelium, root conditioning, bacterial reduction and decontamination of infected implant surfaces is discussed, and a summary of the advantages and disadvantages of using lasers for periodontal treatment is provided.